Hubungan Kesejahteraan Dengan Sikap Petani Dalam Menentukan Metode Peremajaan Kelapa Sawit di Kelurahan Kampung Singkep Kecamatan Muara Sabak Barat Kabupaten Tanjung Jabung Timur - Pernanda, Merta; Kemala, Nida; Alawiyah, Wiwin (Jurnal MeA (Media Agribisnis), 2024)
This research was carried out in Kampung Singkep Village, Muara Sabak Barat District, East Tanjung Jabung Regency. This research aims to look at farmers' decisions in determining the rejuvenation method in cultivating oil palm plants that they will carry out. The scope of this research focuses on the relationship between welfare and farmers' attitudes in determining the choice of rejuvenation method. Data collection was carried out in May 2023. The type of data used based on time is cross section data equipped with primary and secondary data. The sample numbered 73 from a population of 275 farmers. The relationship between the two variables above was analyzed using the Chi square analysis tool. The research results showed that the number of prosperous farmers was 61 farmers (83.56%) while the less prosperous farmers were 12 farmers (16.44%). Farmers who chose the total uprooting method were higher than farmers who chose the insert rejuvenation method. The total number of farmers who chose to tumble was 59 farmers (80.82%) while the number of farmers who chose the insert method was 14 farmers (17.18%).  Both less prosperous and more prosperous farmers choose the method of rejuvenation by completely uprooting. There is a relationship between family welfare and farmers' attitudes in determining oil palm rejuvenation methods.Keywords: Oil palm; Welfare;  Rejuvenation; Attitude; Relationship Abstrak. Penelitan ini dilaksanakan di Kelurahan Kampung Singkep, Kecamatan Muara Sabak Barat Kabupaten Tanjung Jabung Timur. Penelitian ini bertujuan untuk melihat keputusan petani dalam menentukan metode peremajaan  dalam budidaya tanaman kelapa sawit yang akan mereka lakukan. Ruang lingkup pada penelitian ini terfokus pada hubungan antara kesejahteraan dengan sikap petani dalam menentukan pilihan metode peremajaan. Pengumpulan data dilakukan dalam bulan Mei 2023. Jenis data yang   digunakan  berdasarkan waktu adalah   data cross section dilengkapi dengan data primer dan sekunder. Sampel berjumlah 73 dari populasi 275 petani. hubungan antara dua variabel di atas dianalisis menggunakan alat analisis Chi kuadrat. Hasil penelitian menunjukkan bahwa jumlah petani sejahtera sebanyak 61 petani  (83,56%) sedangkan petani kurang sejahtera sebanyak 12 petani (16,44%). Petani yang memilih metode tumbang total   lebih tinggi dibandingkan petani yang memilih peremajaan metode sisip. Jumlah petani yang memilih tumbang total sebanyak 59 petani (80,82 %) sedangkan petani yang memilih metode sisip sebanyak 14 petani (17,18%).  Baik petani yang kurang sejahtera maupun yang sejahtera kedua-duanya lebih banyak memilih metode peremajaan dengan tumbang total. Terdapat hubungan antara kesejahteraan     keluarga dengan sikap petani dalam menentukan metode peremajaan kelapa sawit.  Kata Kunci : Kelapa Sawit; Kesejahteraan; Peremajaan; Sikap; Hubungan